An electron-deficient nanosized polycyclic aromatic hydrocarbon with enhanced anion–π interactions. Issue 84 (5th October 2018) - Li, Lei; Hong, Yu-Jian; Lin, Yun; Xiao, Wang-Chuan; Lin, Mei-Jin
Abstract : A super-electron-deficient nano-sized polycyclic aromatic hydrocarbon with six imide groups at the corners has been synthesized, which exhibited enhanced anion–π interactions with various anions. Abstract : A super-π-acidic nanosized polycyclic aromatic hydrocarbon with six imide groups at the corners was prepared from the pre-synthesized 7, 8-dichlorobenzo[ghi]perylenetriimide through a combination reaction of Ullmann-type and C–H transformation, which exhibited enhanced anion–π interactions with various anions.